2008
DOI: 10.1093/cjres/rsm009
|View full text |Cite
|
Sign up to set email alerts
|

Models for university technology transfer: resolving conflicts between mission and methods and the dependency on geographic location

Abstract: The conversion of University research into economic growth is vital for the future of many nations. In order to improve the efficiency of this transfer we have looked at the effectiveness of tech transfer activity in the US. Our research indicates that Universities that are not located in a region supportive of entrepreneurs should modify their mission and methods for technology transfer. Using both quantitative and qualitative methods, the authors develop an overview of the problem and recommend three new str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
1
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 19 publications
0
39
1
2
Order By: Relevance
“…These policy implications echo those of Warren et al (2008) who propose that, with respect to universities, policymakers should develop 'supportive innovation systems' for their locales, appropriate to the need of the firms within them. For instance, smart online services to match potential partners may be tailored towards the needs of particular types of firm, with smaller KIBS firms being perhaps best directed towards local universities.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…These policy implications echo those of Warren et al (2008) who propose that, with respect to universities, policymakers should develop 'supportive innovation systems' for their locales, appropriate to the need of the firms within them. For instance, smart online services to match potential partners may be tailored towards the needs of particular types of firm, with smaller KIBS firms being perhaps best directed towards local universities.…”
Section: Discussionmentioning
confidence: 72%
“…While previous work has shown that university knowledge spillovers are effective at distances of between 97 Km and 161 Km (Woodward et al 2006;Warren et al 2008;Hausman 2012) the following analysis utilises a lower threshold to deliberately capture the intra-urban nature of collaborative network linkages in the UK. The UK is a densely populated nation, with an urban population density of over 4300 per KM, compared with around 430 for the country as a whole (ONS, 2013 …”
Section: Dependent Variablementioning
confidence: 99%
“…Transferors might include: universities; researchers; university scientists; technology transfer office (TTO); public universities; educational and research institutions; technological portfolio company; public technology company; knowledge and technology transfer organisations; PRO. Transferees might include: client companies; spin-offs and start-ups; entrepreneurs in business; researchers and industry project manager; all parties involved in the organisation: senior management, middle management, engineers, support, marketing and sales; inventors and future users of technology (Siegel et al, 2004;Gorschek et al, 2006;Harmon et al, 1997;Necoechea-Mondragón et al, 2013;Genet et al, 2012;Seaton and Cordeyhayes, 1993;ATTC Network, 2011;Gross, 2003;Landry et al, 2013;Heinzl et al, 2013;Warren et al, 2008).…”
Section: A Generic Kttmmentioning
confidence: 99%
“…Agents might include: TT company; non-profit organisation (NPO); industry liaison offices; communities of practice; TTO; federal agencies; direct links and dyadic alliances, among others (Siegel et al, 2004;Gorschek et al, 2006;Harmon et al, 1997;Necoechea-Mondragón et al, 2013;Genet et al, 2012;Seaton and Cordeyhayes, 1993;ATTC Network, 2011;Gross, 2003;Landry et al, 2013;Heinzl et al, 2013;Warren et al, 2008).…”
Section: A Generic Kttmmentioning
confidence: 99%
“…Therefore, the actual definition of technology transfer efficiency may vary according to research objectives. Warren et al (2008) argue that a 'one size fits all' approach cannot be achieved which points out to the multifarious nature of UTTOs efficiency.…”
Section: Efficiency Evaluation Of Uttosmentioning
confidence: 98%